Screening prefrailty in Japanese community-dwelling older adults with daily gait speed and number of steps via tri-axial accelerometers - Naoto Takayanagi (Nature Portfolio, 2021)
Abstract Prefrailty is an intermediate stage between non-frailty and frailty. It is associated with an increased risk of progression to frailty, which makes it important to screen older adults for prefrailty at an early stage. This study verified whether daily gait speed and number of steps measured using a tri-axial accelerometer could be used to identify prefrailty. In total, 1692 Japanese community-dwelling older adults were divided into robust (n = 1032) and prefrail (n = 660) groups based on the Kihon Checklist, which is a self-administered questionnaire. Both daily gait speed and number of steps were measured for two weeks using tri-axial accelerometers. We also calculated the area under the ROC curve and the cut-off values for these parameters. Our results showed that the cut-off value for daily gait speed was 106.3 cm/s, while that for number of steps was 6342.2. In addition, we found that the combined assessment of both cut-off values was a more effective way to screen older adults with prefrailty status compared to either parameter alone. This is also considered an effective way to reduce national expenditures for daily care assistance.